Hydrologic remediation for the Deepwater Horizon incident drove ancillary primary production increase in coastal swamps. Issue 5 (30th March 2015) - Middleton, Beth A.; Johnson, Darren; Roberts, Brian J.; Boudell, Jere A.; Dixon, Mark D.; Rood, Stewart B.; Stromberg, Juliet C.
Abstract As coastal wetlands subside worldwide, there is an urgency to understand the hydrologic drivers and dynamics of plant production and peat accretion. One incidental test of the effects of high rates of discharge on forested wetland production occurred in response to the 2010 Deepwater Horizon incident, in which all diversions in Louisiana were operated at or near their maximum discharge level for an extended period to keep offshore oil from threatened coastal wetlands. Davis Pond Diversion was operated at six times the normal discharge levels for almost 4 months, so that Taxodium distichum swamps downstream of the diversion experienced greater inundation and lower salinity. After this remediation event in 2010, above‐ground litter production increased by 2.7 times of production levels in 2007–2011. Biomass of the leaf and reproductive tissues of several species increased; wood litter was minimal and did not change during this period. Root production decreased in 2010 but subsequently returned to pre‐remediation values in 2011. Both litter and root production remained high in the second growing season after hydrologic remediation. Annual tree growth (circumference increment) was not significantly altered by the remediation. The potential of freshwater pulses for regulating tidal swamp production is further supported by observations of higher T. distichum growth in lower salinity and/or pulsed environments across the U.S. Gulf Coast. Usage of freshwater pulses to manage altered estuaries deserves further consideration, particularly because the timing and duration of such pulses could influence both primary production and peat accretion. © 2015 The Authors. Ecohydrology published by John Wiley & Sons Ltd.